Pengembangan UMKM Abon Ikan Patin Sebagai Ketahanan Pangan di Kepenghuluan Rantau Bais, Kecamatan Tanah Putih, Kabupaten Rokan Hilir - Fanny Septya; Abul Subki Annadawi; Anlili Ansari Lasmiadi; Azka Rabila; Aztyara Syahida; Desi Sapitri; Haidar Labib Khairy Wimanjaya; Muhammad Fariza; Rahma Dani; Saripah Aini (Jurnal Kabar Masyarakat, 2023)
Rantau Bais Kepenghuuan has quite potential catfish ponds, usually the results of catfish ponds are sold in the form of fresh fish without any management so that management of catfish can increase the added value of catfish and become a productive economic potential for SMEs. The outreach and shredded making activities were carried out on August 12 2023 with the target community being 34 young people from Rantau Bais Penghuluan, Tanah Putih District, Rokan Hilir Regency. The aim of this outreach is to create catfish-based products, provide information and training to improve community skills in processing catfish and develop local products by mobilizing MSMEs. The methods used are counseling, training and assistance in the process of making catfish floss right through to packaging under the Karabon23 brand and marketing. The results of the activities were the formation of a group of shredded catfish producers.